A survey-based assessment of perceived flood risk in urban areas of the United States. (December 2019) - Harlan, Sharon L.; Sarango, Mariana J.; Mack, Elizabeth A.; Stephens, Timothy A.
Highlights: In a sample of US urban residents, 27.5% had experienced a major flood in their lifetimes. Socially vulnerable people were more likely to perceive higher risks of future floods. Greater potential exposure to flood hazard increased the odds of perceiving higher flood risk. Personal flood experience and greater exposure to flood news increased perceived flood risk. Experiencing > 1 major flood doubled the odds of perceiving higher flood risk. Abstract: How people perceive the risks of climatic hazards is currently a major research thrust in the field of risk perception. In the wake of recent flood disasters in the United States (US) and globally, more researchers are investigating social vulnerabilities as well as the role of cognition in explaining risk perceptions. This study analyzed how people in the US perceive the risk (i.e., likelihood and seriousness) of flooding via a layered analysis that considered several plausible and intertwined lines of inquiry from the risk perception literature. We surveyed 9250 individuals within nine major urban areas, including the largest city and one smaller city in each region. The National Flood Hazard Layer product provided data for deriving their potential exposure to flood hazards. The analyses tested and confirmed several hypotheses drawn from Social Vulnerability Theory and from Protective Motivation Theory: characteristics associated with social vulnerability (older, female, race/ethnic minorities, low income), previous experiences with and awareness of flood news, and potential exposure to flood hazard (local fraction of flood prone area) significantly increased risk perceptions of floods. Self-confidence in ability to cope with a future flood disaster lowered risk perceptions. This study is the first snapshot of flood risk perceptions nationwide in the US. It points to needs for more theoretically-driven research about flood risk perceptions and behaviors, flood risk communication within local communities, and more social and economic support for vulnerable populations.